Peningkatan Kapasitas Pemandu Wisata Masyarakat Lokal dalam Pengelolaan Keanekaragaman Hayati Fauna di Kampung Wisata Rhepang Muaif (KWRM), Kabupaten Jayapura - Menufandu, Herlina; Surbakti, Suriani Br.; Wattilete, Jeirel; Panjaitan, Raini; Yembise, Yohanna; Ramandey, Erlies P.; Pahabol, Evelin; Tebay, Natalia K. (Bakti Hayati: Jurnal Pengabdian Indonesia, 2025)
Rhepang Muaif Tourism Village is home to a variety of charming fauna and flora. In the development of natural tourism, this charm becomes enchanting with the presence of trained tour guides. This community service activity is very useful, namely providing training for Rhepang Muaif birdwatching tour guides in the utilization of natural resources, especially fauna, which was introduced in an interesting way using a local knowledge approach by recognizing and understanding the behavior of several animals especially birds of paradise, and providing responsive information to visitors as an effort to develop the Tourism Village to support the existence of Rhepang Muaif birdwatching. The methods used in implementing this community service activity include preparation, delivery of materials, as well as practice and evaluation. The results of the training showed a significant increase in the knowledge and skills of the guides. In addition, other expected positive impacts are an increase in the number of tourist visits, and increased income for managers and local communities